Securing the State through the Production of 'Global' Citizens: Analyzing Neo-Liberal Educational Reforms in Jordan and the USA. (March 2014) - Hantzopoulos, Maria; Shirazi, Roozbeh
From a human capital perspective, schooling has long represented an engine of economic growth, individual advancement, and competitiveness in the global market. In recent years, this theorization of schooling has become linked with articulations of national security in both the Global North and South, as policymakers, private sector actors, and international donor agencies frequently describe economic growth and opportunities for individual advancement as requisites to social and political stability. Lost amid the current US foreign policy discourses about the Middle East is an analysis of how neo-liberal educational reforms in both regions are similarly reconfiguring relationships between the nation-state and its young citizens. In critically interrogating how the sociopolitical work of schooling is articulated in Jordanian and American education policy texts, this article argues that neo-liberal discourses of 'choice', 'accountability' and 'participation' in current regimes of education reform seemingly produce new formations of citizenship locally (national security) and globally (global citizenship). Yet, this reordering of civic relationships serves to reify the (economic) interests of the nation-state and maintain a specific global hegemonic order. However, the article also highlights ways in which peoples' movements in the United States of America (USA) and Jordan are challenging the notions that these policies are merely tacitly accepted by most.